2012
DOI: 10.1021/la3011162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chirality and Length on the Penetrability of Single-Walled Carbon Nanotubes into Lipid Bilayer Cell Membranes

Abstract: The ability of carbon nanotubes to enter the cell membrane acting as drug-delivery vehicles has yielded a plethora of experimental investigations, mostly with inconclusive results because of the wide spectra of carbon nanotube structures. Because of the virtual impossibility of synthesizing CNTs with distinct chirality, we report a parametric study on the use of molecular dynamics to provide better insight into the effect of the carbon nanotube chirality and the aspect ratio on the interaction with a lipid bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 48 publications
3
35
0
Order By: Relevance
“…23, 28,29 Larger diameter CNTs disrupt the bilayer to a larger extent and allow more interactions with the membrane during simulations, therefore requiring larger forces to move through the bilayer. 28,29 Moreover, CNTs shorter than the membrane thickness (∼60 Å) are more likely to rotate while moving through the bilayer. 28 Very few studies exist on the uptake mechanism of BNNTs.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23, 28,29 Larger diameter CNTs disrupt the bilayer to a larger extent and allow more interactions with the membrane during simulations, therefore requiring larger forces to move through the bilayer. 28,29 Moreover, CNTs shorter than the membrane thickness (∼60 Å) are more likely to rotate while moving through the bilayer. 28 Very few studies exist on the uptake mechanism of BNNTs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…28,29 Moreover, CNTs shorter than the membrane thickness (∼60 Å) are more likely to rotate while moving through the bilayer. 28 Very few studies exist on the uptake mechanism of BNNTs. Ciofani and colleagues 7,17,19 found that uptake of polyethylenimine-coated and poly-L-lysine-coated BNNTs was via energy dependent endocytosis, and attributed this to the chemical reactivity of the polyethylenimine coating.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Computational studies have mainly focused on the self-assembly of SWNTs and surfactants (or lipids) [143,[150][151][152][153][154], and the interaction between SWNTs and lipid bilayers [155][156][157][158][159][160][161][162][163][164][165][166][167][168]. Simulations have shown that the self-assembly of SWNTs and their interactions with lipid bilayers can be modulated by the structure and concentration of surfactant, and the size and chirality of SWNT.…”
Section: Simulations Of Pegylated Carbon Nanotubesmentioning
confidence: 99%
“…Because of this 'hydrophilic-hydrophobic-hydrophilic' structure, cell membranes present a formidable barrier to most polar molecules. This means an interface between the artificial materials and the lipid bilayer must be created and surfaces of nanostructures will progressively disrupt the organization of the biomolecules when they come into contact with cell membrane [14][15][16][17][18][19]. Though, numerous experimental platforms employing nanoscale structures have been constructed to deliver various molecules into different types of cells [2,5,11,[20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…However, when building such platforms, researchers usually focus on their geometrical size [24], shape [25] or the biological effectors [2] coated on them, and typically pay little attention to the interfaces between the artificial materials and the biological bilayer or the damage experienced by the membrane. In reality, different interfaces will lead to different degrees of bilayer disruption [16,19,25] some causing cell death [22,26]. It is widely accepted that in many cases it is the coated molecules that are interacting with biological system [27][28][29].…”
Section: Introductionmentioning
confidence: 99%